The effects of angiotensin-converting enzyme inhibitors in heart recipients: a single center experience - А. О. Shevchenko; R. A. Faradzhov; D. A. Izotov; N. N. Koloskova; Е. A. Nikitina; O. E. Gichkun; V. I. Orlov; I. Yu. Tunyaeva; B. L. Mironkov (Вестник трансплантологии и искусственных органов)
Aim. To study the effect of ACE inhibitors (ACEI) in heart recipients on the prognosis and myocardial remodeling.Materials and methods. Three hundred and eighty-six patients who received orthotopic heart transplantation (HT) were consequently enrolled to the study from February 2009 to November 2016.Results. Thirty days after the HT, ACEIs were assigned to 141 recipients. Arterial hypertension was diagnosed in all cardiac recipients who received ACEI and among 48 patients (19.5%) from non-ACEI group. Patients receiving ACEI had significantly better event-free survival than control group (p = 0.045) during the follow-up for 1361,6 ± 36,9 days. Left ventricle (LV) end-diastolic dimension did not change over the time in both groups, whereas LV posterior wall thickness in non-ACEI group significantly increased from 1.35 ± 0.03 cm to 1,23 ± 0.05 cm (p < 0.05).Conclusion. Cardiac recipients who received ACE inhibitors had better survival and less transplant left ventricle progression, that could reflect beneficial effects of renin-aldosterone-angiotensin system inhibition after heart transplantation.